PENGGUNAAN SHEET PILE SEBAGAI PERKUATAN TEBING SUNGAI DONDANG DI LOKASI PROYEK BLC2 PT. KUTAI ENERGI, KABUPATEN KUTAI KARTANEGARA, KALIMANTAN TIMUR - Arief Nugraha Pontoh; Muhammad Fachri W. Ramadhan (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2022)
The collapse of the banks of the Dondang river at the BLC2 project site of PT. Kutai Energi caused the barge to not dock and the conveyor to be unusable. One of the causes of landslides is changes in river water levels which cause the soil around the river banks to become saturated and unstable. The research begins with a survey and data collection related to the research location. Analysis using GeoStudio (Slope/W) 2012 software was carried out with two models, namely when the river water level is normal and when the river water level is in a flooded condition. The results of the analysis show that the critical condition occurs in the second condition where the river water level is in a flood condition. In these conditions, it is known that in the existing condition of the slope without reinforcement, the value of safety number (SF) = 1.125 is obtained. On the other hand, when the pile reinforcement is given, the slope safety score increases to 1.741 which indicates that the plaster can overcome the sliding on the cliff due to the influence of the river water level